Methodology and Policy of Designing and Implementing the National Qualification System - A. N. Leybovitch (Образование и наука)
The paper looks at the current research in the field of the new qualification system development, procedures and outcomes of devising its elements and their influence on vocational training development. The author takes the methodology of the system analysis in the labor and training spheres as the scientific basis for solving the above problems.The main emphasis is on the new approach, which provides the comprehensive analysis of the integrated and complete labor process instead of the in-depth analysis of separate specialties. The above approach was developed and applied in the methodological schemes for creating the national qualification framework and professional standards. The research findings include defining the functions and goals of the new qualification system; methodology tools for its formation; current analysis and immediate tasks of the state policy concerning the given sphere. The research is aimed at the practical application of the Russian vocational training at all levels in the course of modernization. The necessary methodology basis is given for devising a new structure of vocational training system, as well as the new generation of educational programs meant to meet the demand for the personnel in the modern Russian economy. The necessity of integrating the approach to labor and training on a new methodological basis is substantiated. The introduction of the new qualification framework should correspond with the changes in the assessment mechanism of training outcomes. The existing legal base of the Russian system of vocational training, unable to correlate the vocational training and economy, should be further developed.